PENINGKATAN KUALITAS PRODUK MINUMAN IKM MELALUI PENGENDALIAN PROSES PRODUKSI DAN HIGIENITAS - Noya, Sunday; Taneo, Stefanus Yufra. M.; ., Melany (Jurnal Pengabdian Masyarakat Charitas, 2022)
Small and Medium Enterprises (SMEs) are the largest business entities in Indonesia. Of this very large number, the largest proportion of SMEs is engaged in food and beverage production. Unfortunately, with such a large number, the awareness to apply food safety and hygiene standards in the SME production process is still considered very low. The results of our study found that one of the factors that affect product quality and competitiveness of SME is production process control and hygiene. The results of this research were then applied to a community service program for beverage SMEs in Malang Regency in the form of training on good and hygiene processed food production methods. The results of statistical tests and further observations carried out on the training participants found that this community service program was effective in increasing SMEs knowledge about good production methods, hygiene, and sanitation as well as bringing positive changes to their production systems which are expected to further improve product quality and competitiveness of SMEs.